Pemberlakuan Wajib Sertifikasi Halal Pada Produk Luar Negeri Di Indonesia Berdasarkan Peraturan Pemerintah Nomor 39 Tahun 2021 Terhadap Technical Barrier To Trade Agreement - Hafiz, Muhammad; Jayakusuma, Zulfikar; HZ, Evi Deliana (Jurnal Ilmiah Wahana Pendidikan, 2024)
Cross-border trade has existed for a long time and is growing rapidly. The World Trade Organization (WTO), founded in 1995, regulates international trade with principles inherited from GATT. Indonesia, as a member of the WTO, implements halal certification obligations for foreign products in accordance with Government Regulation no. 39 of 2021. However, this implementation can create trade barriers involving differences in requirements, costs, infrastructure limitations and consumer trust. This research aims to find out how the implementation of mandatory halal certification in Government Regulation no. 39 of 2021 on foreign products in Indonesia and to find out whether the implementation of mandatory halal certification in this regulation is an obstacle to trade from the perspective of the Technical Barrier to Trade Agreement. This research uses a type of normative juridical research which is also known as a literature approach. In addition, this research uses a comparative legal research model in which in this research there are two legal sources that are compared, namely Government Regulation no. 39 of 2021 and Technical Barrier to Trade Agreement. The research results show that the implementation of mandatory halal certification on foreign products through Government Regulation no. 39 of 2021 does not constitute an obstacle to trade from the perspective of the Technical Barrier to Trade Agreement because it aims to protect human health and protection for the Indonesian Muslim community as stated in article XX (b) of the TBT Agreement. The existence of Government Regulation no. 39 of 2021 which regulates halal certification obligations and its implementation for foreign products in Indonesia is actually in line with the principles of the TBT Agreement (Technical Barriers to Trade). In the context of the TBT Agreement, the government has the right to regulate products to maintain public health and safety and to ensure compliance with halal principles which are a religious requirement in Indonesia.